The Implementation of Student Teams-Achievement Division (STAD) in Teaching Reading Comprehension in Discussion Text for Senior High School Student - Ririn Oktarina; Fitrawati Fitrawati (Journal of English Language Teaching, 2018)
This paper is aimed to discuss about the use of Student Teams-Achievement Division (STAD) technique in teaching reading comprehension in discussion text for senior high student. This strategy is expected to help the student to understand the text. The activity done by the teacher and students can be classified into four steps. First, the teacher presents a lesson via textbook, picture, or using laptop or in focus. Second, the teamwork consists of four or five students who represent a cross-section of the class in terms of academic performance, sex, and race or ethnicity. Each teamwork presents their material. Third, students take quiz. Fourth, the teacher gives the score for each group from their discussion in front of the class and members’ individual quiz scores. Finally, the teacher gives the reward, such as certificate for the group who get the highest score. After applying this strategy, the students are expected to comprehend the discussion text.